MODEL BERMAIN TERSTRUKTUR BERBASIS WALKING LINE UNTUK MEREDUKSI DISTRAKSI BELAJAR ANAK USIA 3-4 TAHUN - Mufidah, Nailul; Rosfalia, Nihna Atho'a (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the contribution of implementing a structured play model based on the walking line activity in reducing learning distractions among children aged 3–4 years at KB Dewi Masyithoh I. The research employed a descriptive qualitative approach, with data collected through observations, teacher interviews, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing The results show that the regular implementation of the walking line activity can reduce learning distraction behaviors among children aged 3–4 years. The decrease was observed in several indicators, including reduced running behavior inside the classroom, reduced talking outside the context of learning activities, and increased responsiveness of children to teacher instructions during the learning process. In addition, children demonstrated better ability to maintain focus and complete learning activities until the end. Therefore, the structured play model based on the walking line activity can be an effective learning strategy to help reduce learning distractions in early childhood when implemented consistently in classroom activities.